E-059 A Novel approach for carotid sacrifice using temporary balloon occlusion and Onyx in a porcine model. (16th November 2010) - Sivapatham, T; Teng, Q; Spiotta, A; Hussain, M; Moskowitz, S; Hui, F
Abstract : Introduction: Carotid sacrifice is a valuable technique in the treatment of giant internal carotid artery aneurysms, carotid cavernous fistulae and carotid blowouts. With detachable balloons no longer available in the USA, most neurointerventionalists have relied on coil embolization as their primary means for carotid sacrifice, a procedure that can be lengthy and expensive. We describe a new technique for carotid sacrifice using temporary balloon occlusion of the carotid artery while embolizing the artery with Onyx in a porcine model. Materials and methods: Following strict animal laboratory protocols, a total of 10 vessels were embolized in four pigs. The pigs were placed under general anesthesia and continuously monitoring by the animal laboratory veterinary staff. Access into the common femoral artery was gained using a micropuncture kit, and a 7 F sheath was placed. A 7 F guiding catheter was advanced over a 0.035 inch glidewire under fluoroscopic guidance into the right or left common carotid artery. A double Tuohy–Boorst was attached to the hub of the guiding catheter. An over the wire balloon was placed through one side port of the Tuohy–Boorst and advanced over a 0.010 inch microwire into the common carotid artery. An Onyx compatible microcatheter was then advanced through the second side port of the Tuohy–Boorst over a 0.010 inch microwire to a position adjacent or just distal to the balloon. The balloon was inflated and contrast injected through the guide catheter to confirm complete occlusion of flow. Onyx was then slowly injected under blank roadmap guidance into the common carotid artery through the microcatheter until a dense Onyx cast was visualized. Once the desired result was obtained, the microcatheter was removed and then the balloon was deflated and removed under fluoroscopic guidance. Follow-up angiography was performed. In four vessels, one or two coils were detached through the microcatheter, distal to the balloon, prior to Onyx embolization. In two vessels, the Ascent balloon catheter was used and Onyx embolization done directly through the balloon catheter. Results: Successful occlusion of the carotid artery was obtained in eight of 10 vessels using the techniques described above. In the two unsuccessful vessels, we were able to identify deficiencies in our technique that led to the failures (premature removal of the balloon prior to formation of a dense Onyx cast in one vessel and detachment of a single coil as opposed to two coils in the other vessel). Conclusion: Carotid sacrifice using Onyx with temporary balloon occlusion is a safe and effective technique, and can be performed more rapidly than the traditional method of coil embolization.